2023
DOI: 10.3390/polym15183780
|View full text |Cite
|
Sign up to set email alerts
|

Improving Sustainability through Covalent Adaptable Networks in the Recycling of Polyurethane Plastics

Edoardo Miravalle,
Pierangiola Bracco,
Valentina Brunella
et al.

Abstract: The global plastic waste problem has created an urgent need for the development of more sustainable materials and recycling processes. Polyurethane (PU) plastics, which represent 5.5% of globally produced plastics, are particularly challenging to recycle owing to their crosslinked structure. Covalent adaptable networks (CANs) based on dynamic covalent bonds have emerged as a promising solution for recycling PU waste. CANs enable the production of thermoset polymers that can be recycled using methods that are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…Besides, during the last years, the incorporation of reversible covalent bonds into their structure has been presented as a promising alternative to make polyurethanes more recyclable and reprocessable. 9,10 One of the most studied reversible covalent bonds is based on Diels−Alder (DA) chemistry, which consists of a chemical coupling reaction between a conjugated diene and a substituted alkene, commonly termed the dienophile, to form a substituted cyclic derivative. 11 For instance, the Diels−Alder reaction between furan and maleimide is thermally reversible, and takes place at low temperatures, while its reversal (retro-DA) occurs at higher temperatures.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, during the last years, the incorporation of reversible covalent bonds into their structure has been presented as a promising alternative to make polyurethanes more recyclable and reprocessable. 9,10 One of the most studied reversible covalent bonds is based on Diels−Alder (DA) chemistry, which consists of a chemical coupling reaction between a conjugated diene and a substituted alkene, commonly termed the dienophile, to form a substituted cyclic derivative. 11 For instance, the Diels−Alder reaction between furan and maleimide is thermally reversible, and takes place at low temperatures, while its reversal (retro-DA) occurs at higher temperatures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As a solution, scientists have been looking for better methods of final disposal, some of which include physical and chemical recycling. Besides, during the last years, the incorporation of reversible covalent bonds into their structure has been presented as a promising alternative to make polyurethanes more recyclable and reprocessable. , …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported potential, alternative PU recycling strategies that convert traditional static PU networks into thermally reprocessable, dynamic covalent adaptable networks (CANs) by incorporating Lewis acid catalysts such as dibutyltin dilaurate (DBTDL), either during the synthesis of new PUs or before reprocessing postconsumer PUs. The incorporated catalysts trigger dynamic carbamate exchange reactions at elevated temperatures (typically 180–220 °C), enabling these PU CANs to reshape under stress like thermoplastics during conventional melt-state processing such as compression molding and twin-screw extrusion, similar to many other CANs and vitrimers. In contrast, at lower service temperatures, these PU CANs maintain network structures and thermomechanical robustness like traditional PU thermosets. With this approach, Dichtel and co-workers reprocessed waste cross-linked PUs (e.g., PUFs) into recycled PU films/filaments with equivalent network structures and properties, through a bulk (i.e., solvent-free), continuous twin-screw extrusion process . More recently, they further demonstrated a circular foam-to-foam recycling process, which simultaneously combines twin-screw extrusion with foaming to convert originally cross-linked PUFs into next-generation cross-linked PUFs with comparable porous microstructures and compression properties …”
Section: Introductionmentioning
confidence: 99%
“…Despite the advantages of this dynamic carbamate exchange-enabled recycling approach, including circularity and high energy/atom efficiency, previous studies have been limited to thermoset-to-thermoset reprocessing of PU CANs. The percolated network structures and associated high viscosities of these PU CANs pose challenges to their processing and engineering for certain applications that require low-viscosity liquid precursors, such as coatings, adhesives, and sealants. ,, Of greater utility would be a scalable recycling/upcycling strategy that can convert postconsumer cross-linked PUs into a library of materials/products with similar or even higher values for diverse applications. For example, it would be attractive if one can upcycle waste cross-linked PUs into readily processable/soluble and functionalized PUs toward high-end specialty applications, such as photocurable liquid PU resins that can be used for conformal coatings and vat photopolymerization-based additive manufacturing (i.e., 3D printing). , …”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, the typical methods are the addition of dismountable agents (i.e., nanoparticles, thermally expandable particles, additives, etc.) and the chemical modification of the polymer chain by introducing reversible bonds [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%